The Effect of Health Insurance Reform: Evidence from China - Huajing He; Patrick J. Nolen (Institute of Labor Economics (IZA), 2018)
This paper estimates the impact of a health insurance reform on health outcomes in urban China. Using the China Health and Nutrition Survey we find that this reform increases the rate of health insurance coverage significantly among workers in Non-State Owned Enterprises. The double difference (DD) estimations show that the reform also leads to better health outcomes: workers are less likely to get sick and more likely to use preventive care. Using an instrumental variable (IV) approach to look at the causal effect of health insurance, we find those with health insurance use more preventive care but do not report significantly better health outcomes, an increase in health care utilisation, or an increase in out-of-pocket medical expenditure.
Keywords: H51; H43; O2; 330; health insurance reform; health outcomes; China